SENAM FANTASI TERHADAP KEMAMPUAN MOTORIK KASAR ANAK AUTIS DI SDN INKLUSI - mustika sari, Firda (Jurnal Pendidikan Khusus, 2016)
Abstract: Gross motor development associated with the child’s development which motor abilities often associated with the exercise that aims to develop aspects of physical fitness, motor skills, critical thoughts, social, reasoning, emotion, moral value as well as healthy life that is tailored to the child’s characteristics. The purpose of this study relates to exercise gross motoric skills in children with autism through learning “senam fantasi”, because “senam fantasi” can be fun activity for children with autism in accordance with their characteristic, where children can perform the spontaneously beautiful movements, express theirself while listening or feeling a certain rhythm. This study uses a quantitative approach with the design the one group pretest posttest design. The Samples are autistic children in SDN Tebel Gedangan. This research was conducted in 12 meetings. Data collection technique used tests and observation. Data analysis by using test Wilcaxon. The results showed that the senam fantasi significantly affects gross motoric skills in children with autism in SDN Tebel Gedangan. It is based on the results of the study before it is applied senam fantasi gained an average of 42.85, and after senam fantasi was implemented, it obtained an average of Thitung = 0 lebih kecil dari Ttabel = 2 with 5% significance level with N=7 is 2, means Thitung = 0 < Ttabel =2. Based on these results, it is proved that senam fantasi affect gross motoric skills in children with autism in SDN Inklusi Tebel Gedangan Keywords: Autism, senam fantasi, gross motor